A retrospective study of paraganglioma of the urinary bladder and literature review - Zhao, Yi; Zhang, Zhijun; Wang, ShiJun; Wen, Jin; Wang, Dong; Ji, ZhiGang; Zhang, YuShi; Li, HanZhong (Frontiers in Surgery, 2024)
Objective: To retrospect and summarize the characteristics and therapy of paraganglioma of the urinary bladder (PUB). Method: Patients who underwent the operation in Peking Union Medical College Hospital from January 2012 to December 2021 were reviewed for this retrospective study. Results: A total of 29 patients, comprising 9 males (31%) and 20 females (69%) were included. The main manifestations were hypertension, palpitation, and micturition syncope. 8 patients had an increased 24-hour urinary catecholamine, and 7 of them were increased norepinephrine. 7 patients' normetanephrine were increased. 6/18 metaiodobenzylguanidine and 8/22 octreotide imaging were positive. 15 cases took laparoscopic partial cystectomy and 14 took transurethral resection of bladder tumor. Of all the patients, the immunohistochemical index of Melan-A, AE1/AE3 and α-inhibin were negative, while (chromogranin A) CgA, S-100 and (succinate dehydrogenase) SDHB were positive. Ki-67 of 28/29 cases are under 5%, and 1 case whose Ki-67 was 20% was diagnosed with malignant PUB. 27 patients had a regular follow-up, 2 patients were lost found, 3 patients had a recurrence and 1 of these patients died within 1 year of surgery. The symptoms all disappeared or relieved after the surgery. Conclusion: Transurethral surgery approach fits for PUB tumors whose sizes are under 3cm or that protrudes into the bladder and can significantly reduce the postoperative hospital stay. Early detection and treatment are effective, and regular review is necessary after the surgery.